Penghijauan Sebagai Upaya Meningkatkan Kesadaran Masyarakat Tentang Pentingnya Menjaga Lingkungan Dalam Menunjang Kelestarian Alam Di Desa Mata, Kecamatan Taranu Sumbawa. - Wahyuni, Dewi; Firdaus, Andrian (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2023)
Greening carried out in mata village is one of the important activities that must be carried out conceptually in dealing with the environmental crisis. Based on the PKM in mata village, it is necessary to hold a swot analysis, and determine an activity for this PKM, the author holds a program to preserve nature to maintain nature in the village of beautiful eyes, so this program aims to provide knowledge about the importance of greening and preserving nature to the community. The implementation of this PKM uses a method that consists of several stages of implementation, namely the preparation stage, implementation in the form of a preparation process, activities and training, then evaluation. The result obtained from the PKM discussion is that the service is carried out by conducting a needs analysis in the eye village of taranu district. The delivery of material in the form of learning to the eye village community and given training is carried out directly in an orderly and relaxed manner so that participants can digest information easily and feel comfortable to ask questions about the things presented.